Divergent host plant utilization by adults and offspring is related to intra‐plant variation in chemical defences. Issue 11 (28th July 2019) - Mason, Charles J.; Long, David C.; Lindroth, Richard L.; Hoover, Kelli
Abstract: Adult and juvenile herbivores of the same species can use divergent feeding strategies, and thus may inhabit and consume different parts of the plant. Because the expression of chemical defences often differs between host plant tissues, this variation may result in disparate performance outcomes for adult and juvenile conspecifics that feed on distinct dietary substrates. The goal of this study was to evaluate how host range may differ between adults and juveniles in a generalist herbivore. We addressed the impacts of among‐ and within‐plant defence variation using the wood‐feeding Asian longhorned beetle ( Anoplophora glabripennis ) and three host plants having a range of putative resistance. Impacts of host plants on adult and offspring performance were assessed using a series of controlled bioassays. We evaluated adult‐feeding and egg‐laying behaviours in choice and no‐choice experiments using the different hosts, and subsequent offspring establishment. We then evaluated host plant chemical composition related to nutrition and defence. Different plants had strong impacts on adult performance, but these patterns did not extend to effects on offspring. Females were capable of developing eggs when provided Acer rubrum, but not Populus deltoides or Populus tomentosa . Females that produced eggs by feeding on A. rubrum, however, deposited eggs into all three plant species. Larvae hatched and consumed tissues in all three hosts. The differences between adult and juvenile utilization of Populus spp. were reflected in markedly higher salicinoid phenolic concentrations in bark (>2% dw), while wood had trace quantities. Our results demonstrate that plant resistance mechanisms can differentially act upon adult and juvenile life stages of a polyphagous herbivore when there is differential expression of chemical defences among plant tissue types. Anoplophora glabripennis has been a globally successful invader due in part to its broad host range, and our results suggest a mechanism that permits the beetle to exploit marginally resistant plants. This study has implications for how host range differs between insect feeding stages, which is particularly important for invasive, polyphagous species encountering novel food sources. Abstract : This study demonstrates that variation of chemical expression between‐ and within‐plant substrates affects the patterns of colonization between life stages of herbivorous insects. These results have implications in the inferences of plant resistance, and the mechanisms that herbivores use to exploit diverse resources.